Bibliometric mapping of psychological well-being among children with a visual impairment. (May 2021) - Kúld, Pála B; Kef, Sabina; Sterkenburg, Paula S
Children with a visual impairment experience lower psychological well-being than normative populations. While research on this subject is abundant, an overview is lacking of the methods used and topics commonly studied, to guide future research. The aim was to provide a visual overview of common topics included in psychological well-being research from 2000 to 2018 among children with a visual impairment. We created a bibliometric map with the VOSviewer programme using the text mining functionality to construct and visualise co-occurrences of relevant terms from the titles and abstracts in the included literature. The results show that common subjective terms are behaviour, relationships, attachment and parenting, cerebral visual impairment, cerebral palsy, autism spectrum disorder, and intellectual disability. The common methodological terms include literature and randomized control trials, with the latter restricted to specific terms such as parenting. The conclusions and implications are that the results give insight into the subject terms studied in past years and provide a roadmap for future research in the fields of visual impairment and psychological well-being of children. The topics needing more research are rare disorders, siblings, assistive technology, romantic relationships, bullying, and the frequent cooccurrences of visual impairment with autism spectrum disorders and intellectual disability.